International Auditing Standard (500): “Audit Evidence” and its Role in Achieving Audit Quality - A Field Study on Some Sudanese Audit Firms (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
The main objective of this study is to know the role of ISA (500): "Audit Evidence" in achieving audit quality in Sudan, in addition to showing the extent to which audit offices in the Sudanese business environment apply international standards of auditing in general, and particularly ISA (500). The problem of the study was represented by the lack of interest of some audit offices in applying international auditing standards to improve the quality of audit performance, especially ISA (500) which deal with audit evidence, either due to lack of familiarity with the importance of auditing standards or unwillingness to apply them or inability to obtain sufficient evidence for the audit by losing the audit path. The study adopted inductive approach, historical approach and descriptive analytical approach. To achieve the objectives of the study, (80) questionnaires were distributed to the sample community represented by some Sudanese auditing offices in Port Sudan and Atbara, and were (100%) collected and analyzed. The study found several results, among which that is, external auditor obtains sufficient appropriate audit evidence to reduce audit risk according to ISA (500): “Audit Evidence” contributes to achieving audit quality, and External auditor’s knowledge of the competence of the external source of information and its reputation with regard to information according to the requirements of ISA (500): “Audit Evidence” helps to achieve audit quality. The study also recommended that, there is a need to encourage audit offices in Sudan to adopt international standards of auditing in their work in order to achieve audit quality.